Implementation of Library Management in Improving Excellent Service in Vocational High Schools - Muchlis Anshori; Elynawati Elynawati; Alfatchussadiqin Alfatchussadiqin; Atto’ Maulana (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
Excellent service in school library management is oriented to the satisfaction of library visitors. As one of the service providers, the library is obliged to provide convenience to service users to encourage literacy awareness among students and all school members. This article aims to describe and analyze the planning, implementation, and supervision of excellent service in school library management at SMK Muhammadiyah Magelang City. This research was conducted using a qualitative descriptive research method. The results of this study indicate that first, the library of Muhammadiyah Vocational School in Magelang City carries out planning including budget planning, infrastructure, human resources, and library materials. Second, the improvement of library human resources is carried out on an ongoing basis in order to support service performance. Third, supervision in the library of SMK Muhammadiyah Magelang City is carried out by the Principal of the Head of the Library. Supervision in the library is carried out weekly, monthly, and yearly. So from there, the school is able to analyze what needs need to be given to the library. So, the excellent service carried out by the Muhammadiyah Vocational School in Magelang City has been oriented to the satisfaction of library service users. This can be seen from the planning, implementation, and supervision of excellent services that run optimally.